Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Apotek Sumber Sehat Tentena - Kureu, Nolfin Frisca Christina; Sangkide, Charis E. Fajar; Kawani, Fredrik Bastian (Fakultas Ekonomi Universitas KristenTentena, 2024)
This study aims to examine the effect of service quality on customer satisfaction at Sumber Sehat Tentena Pharmacy. In increasingly fierce business competition, service quality is one of the key factors to increase competitiveness and maintain customer loyalty. Through a survey approach of 30 respondents who visited Sumber Sehat Pharmacy for two months, this study used simple regression analysis techniques to analyze the data. The results showed that service quality has a positive and significant influence on customer satisfaction. The variables of service quality reviewed include aspects of responsiveness and drug availability. These findings emphasize the importance of improving service quality as a key strategy in building customer satisfaction and loyalty.